P3.296 Prevalence of Chlamydial Infections Within Eight South African Provinces (2006–2011). (13th July 2013) - Radebe, F; Maseko, V; Basson, I; Gita, G de; Takuva, S; Lewis, D A
Abstract : Background: The microbiological surveillance was undertaken in eight provinces of South Africa during 2006 –2011 to determine the aetiology of the male urethritis syndrome (MUS), vaginal discharge syndrome (VDS) and genital ulcer syndrome (GUS) and the prevalence of HIV, HSV-2 and syphilis. Methods: 1361 MUS, 1691 VDS and 465 GUS cases were consecutively recruited in eight South African provinces (2006–2011). Laboratory-based diagnostic methods included nucleic acid amplification to detect Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, Trichomonas vaginalis, Herpes Simplex Virus 2, H aemophilus ducreyi, Treponema pallidum and Chlamydia trachomatis serovars L1–3. Results: Overall, 202 (14.9%) MUS and 240 (14.2%) VDS cases were positive for C. trachomatis while 6 (1.3%) GUS cases were positive for C. trachomatis serovars L1–3. The highest prevalence of C. trachomatis was 21.1% in Gauteng among men and 19.4% in women. The prevalence in other provinces was: Mpumalanga (men 18.4%; women 17.4%), Limpopo (men 14.0%; women 16.7%), Eastern Cape (men 16.4%; women 13.5%), Western Cape (men 13.5%; women 14.9%), Northwest (men 10.3%; women 11.1%), Free State (men 8.0%; women 9.8%) and Northern Cape (men 8.1%; women 9.6%). C. trachomatis serovars LI-3 prevalence was 3.2% in the Free State, 2.8% in Mpumalanga and 0.7% in Gauteng. No C. trachomatis serovars L1–3 were detected in other five provinces. Conclusions: The prevalence of C. trachomatis infection was high in this population and remains an important cause of genital infection in South Africa particularly in men. This may fuel the HIV epidemic which was high in most of the provinces in this study.